Emotional Spiritual Quotient (ESQ) Approach and its Relevance to Problem Solving in Individual Counseling: An Examination of Ary Ginanjar Agustian's Thought - Linda Hartini; Jonsi Hunadar; Triyani Pujiastuti (Academia Edu Cendekia Indonesia (AEDUCIA), 2024)
Background: The integration of emotional and spiritual aspects through the ESQ approach is vital in modern counseling, while parental consent for minors remains a crucial ethical and legal concern, questioning its role as a requirement or necessity for effective practice. Objective: This study aims to examine the urgency of the Emotional Spiritual Quotient (ESQ) approach and its relevance in individual counseling practice based on the thoughts of Ary Ginanjar Agustian. Method: This research uses a literature review design using primary and secondary data sources. Data were collected through documentation from books and scientific journals and then analyzed using the content analysis method. Data validity was tested through discussion with peers and triangulation. Results: The ESQ approach offers a new paradigm in counseling, where spiritual values are used as the core in helping individuals face life's challenges. It goes beyond traditional methods, focusing only on emotional and cognitive aspects. Conclusion: The ESQ approach highlights the importance of integrating Emotional Quotient (EQ) and Spiritual Quotient (SQ) to guide individuals in overcoming life's challenges. Contribution: ESQ makes a significant contribution by integrating the spiritual dimension into modern counseling practices, which previously often neglected the aspect of spirituality.